2013
DOI: 10.1108/14676371311288967
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian teacher trainees' practices on science and the relevance of science education for sustainability

Abstract: Purpose -The purpose of this paper is to investigate the practice of teacher trainees on science and the relevance of science education. The study focuses on teacher trainees' practice on science teaching and its relevance to understanding science education. Design/methodology/approach -The study employed a survey method using questionnaires. The samples consist of 80 teacher trainees, majoring in Science Education, from a teachers training institute in Malaysia. The teacher trainees were asked to complete a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The incorporation of ESD into the curricula of preservice teacher training ensures the promotion of sustainability amongst future citizens. This education could be promoted through the teaching of science (Madhawa Nair, Rashid Mohamed, & Marimuthu, 2013), scientific experimentation (Karpudewan, Ismail, & Mohamed, 2009) and initiatives (Henze, 2000) related to Agenda 21 (UN, 1992). However, a case study conducted in five faculties of education in Manitoba Canada noted that, despite the relevant efforts made for the integration of this education into pre-service teacher education institutions, ESD has been poorly incorporated into the curriculum (Falkenberg & Babiuk, 2014).…”
mentioning
confidence: 99%
“…The incorporation of ESD into the curricula of preservice teacher training ensures the promotion of sustainability amongst future citizens. This education could be promoted through the teaching of science (Madhawa Nair, Rashid Mohamed, & Marimuthu, 2013), scientific experimentation (Karpudewan, Ismail, & Mohamed, 2009) and initiatives (Henze, 2000) related to Agenda 21 (UN, 1992). However, a case study conducted in five faculties of education in Manitoba Canada noted that, despite the relevant efforts made for the integration of this education into pre-service teacher education institutions, ESD has been poorly incorporated into the curriculum (Falkenberg & Babiuk, 2014).…”
mentioning
confidence: 99%
“…Strategies to improve environmental education in society should be carried out with the effective support of teachers (Bregeon et al, 2008), or new generations will not transform their mind-sets and take up a respectful attitude to nature (Madhawa Nair et al, 2013). Teachers' environmental knowledge plays a key role in developing the environmental competencies of their students (Mat Said et al, 2003;Guven and Sulun, 2017).…”
Section: Environmental Competencies Of Teachers (Ects)mentioning
confidence: 99%
“…There are four countries that elaborated on this sustainability dimension; Europe by Roorda [14] and Manuel et al [23], the USA by Anthony [18] and Velazquez, Munguia, Platt and Taddei [19], China by Hongwei et al [26] and Malaysia by Wilfredo and Crystal [2], Omidreza et al [4], Rosazman and Velan [13]. On the other hand, Nair et al [3] found that there are needs to educate trainee teachers (male and female) to achieve sustainability in science education.…”
Section: -mentioning
confidence: 99%
“…Keoy, Fadzil and Masnizan [1], Wilfredo and Crystal [2] and Nair, Mohamed and Marimuthu [3]. Additionally, authors identified ten articles that highlighted on sustainable development in Malaysian Research University such as by Omidreza, Elias, Osman and Kamariah [4], Zuhairuse et al [5], Gobi and Rafee Majid [6], Omidreza [7], Mohd, Nur, Muhammad, Ismar and Adi [8], Wan Nur'ashiqin et al [9], Ahmad, Mohammad, Hayati, Hasimah and Masilah [10], Norfadillah, Halimanton and Kamariah [11], Kwami, Che-Ani, Tawil and Basri [12], and Rosazman and Velan [13].…”
mentioning
confidence: 99%